Implementation Of Host Learning In The Course Macroeconomic - Tamboto, Henry J. D.; Manongko, Allen A. Ch.; Sendouw, Recky H. E. (Technium Social Sciences Journal, 2022)
This study aims to analyze Higher Order Thinking Skill (HOTS) oriented learning in the Macroeconomic Theory course at the Economic Education Study Program, Faculty of Economics and Business, Manado State University. This research uses a quantitative approach with experimental methods. The object of research is lecturers and students of the Department of Economic Education, Faculty of Economics and Business, Manado State University. Data were collected through tests, observations, interviews, and documentation and literature studies. The findings of the study are: Inquiry Learning/Learning Model, learning outcomes from Higher order thinking skills (HOTS) can increase in the moderate category with a fairly effective interpretation compared to the control class; using the Problem-based Learning Model (PBL), Higher order thinking skill (HOTS) learning outcomes can be improved compared to control classes with higher average scores of experimental classes than control classes; and Project-based Learning (PJBL), the learning outcomes of higher order thinking skills (HOTS) can be improved compared to the control class with the average experimental class higher than the control class.